2017
DOI: 10.4102/td.v13i1.432
|View full text |Cite
|
Sign up to set email alerts
|

Shifting boundaries of racial space in post-apartheid South Africa: The case of Afrikaner youth in East London

Abstract: South African democracy has brought about changes like freedom of associations, as opposed to apartheid which emphasised separateness of races and cultures. This social change warrants new ways of living among South Africans, especially among young people. Using a qualitative approach with semi-structured interviews, this study examined how white Afrikaans-speaking university students carve out their identities, given the reality that political, social and cultural circumstances have changed in the last two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…https://theologiaviatorum.org Open Access Ntombana and Bubulu (2017) have confirmed that there is still a racial division amongst South Africans, and there are categories of whites, some of whom are willing to shift and others that resist change, away from racist behaviours and practices. This resistance to change is perceived as a modern form of racism (Batts 1989:18).…”
Section: Modern Racism As a Destructive Agent To A Theanthropocosmic Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…https://theologiaviatorum.org Open Access Ntombana and Bubulu (2017) have confirmed that there is still a racial division amongst South Africans, and there are categories of whites, some of whom are willing to shift and others that resist change, away from racist behaviours and practices. This resistance to change is perceived as a modern form of racism (Batts 1989:18).…”
Section: Modern Racism As a Destructive Agent To A Theanthropocosmic Connectionmentioning
confidence: 99%
“…Between 2010 and 2020 there has been the tendency of racial conflicts and racist utterances, from social media to formal debates, in institutions of higher learning in South Africa. These utterances are heard in different provinces in South Africa and are found in institutions of higher learning such as the University of Eastern Cape and the University of Free State (Goga 2010;Ntombana & Bubulu 2017;Soudien 2010). The vandalisation of the image of God was indicated by the incident in which cleaners at the University of the Free State were forced by four white students to eat food that was believed to have been urinated on (Ntombana & Bubulu 2017).…”
Section: Introductionmentioning
confidence: 99%